Of course that is not the whole (toy) story: Entrepreneurship and the cat's cradle - Steyaert, Chris (Journal of Business Venturing, 2007)
Reading and analyzing the Toy Store story imply a critical inquiry into how the act of storytelling can be understood. The entrepreneurial story is situated within the context of the plea to downplay the focus on the individual entrepreneur. As this discussion did not share some of the critical debates on the status of the subject, a narrative study of entrepreneurship might refocus on the storytelling entrepreneur rather than on the process of storytelling. To prevent this, storytelling is conceived as an enacted performance that balances complexity and coherence and that draws upon but is not enclosed by a range of cultural and masternarratives.